DIGITALISASI KUALITAS LAYANAN APLIKASI NEW BIMMA DALAM MENUMBUHKAN MINAT CALON PENCARI KERJA DI DINAS KETENAGAKERJAAN KOTA BANDUNG - Widiya Sri Oktaviani; Tiris Sudrartono (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to understand how the digitization and service quality of the New Bimma application can foster the interest of prospective job seekers. This research was conducted using descriptive qualitative methods with data collection techniques through interviews, direct observation, and literature studies. The data analysis process used includes data collection, data reduction, data presentation, and conclusion. The results showed that the New Bimma application provides various employment-related services in Bandung City and provides benefits for its users. Although not fully known by the public, the quality of this application service is considered good based on indicators of reliability, responsiveness, assurance, empathy, and physical evidence. The app managed to attract 32,469 active users, thanks to an effective promotion strategy on social media. However, the Bandung Manpower Office is advised to still need to increase the frequency of promotions, develop creative content, collaborate with influencers, and conduct periodic evaluations of application performance, user response, and market trends to increase relevant innovations.